Tensions in learning professional identities – nursing students’ narratives and participation in practical skills during their clinical practice: an ethnographic study - Mona Ewertsson; Sangeeta Bagga-Gupta; Renée Allvin; Karin Blomberg (BMC Nursing, 2017)
Abstract Background Clinical practice is a pivotal part of nursing education. It provides students with the opportunity to put the knowledge and skills they have acquired from lectures into practice with real patients, under the guidance of registered nurses. Clinical experience is also essential for shaping the nursing students’ identity as future professional nurses. There is a lack of knowledge and understanding of the ways in which students learn practical skills and apply knowledge within and across different contexts, i.e. how they apply clinical skills, learnt in the laboratory in university settings, in the clinical setting. The aim of this study was therefore to explore how nursing students describe, and use, their prior experiences related to practical skills during their clinical practice. Methods An ethnographic case study design was used. Fieldwork included participant observations (82 h), informal conversations, and interviews (n = 7) that were conducted during nursing students’ (n = 17) clinical practice at an emergency department at a university hospital in Sweden. Results The overarching theme identified was “Learning about professional identities with respect to situated power”. This encompasses tensions in students’ learning when they are socialized into practical skills in the nursing profession. This overarching theme consists of three sub-themes: “Embodied knowledge”, “Divergent ways of assessing and evaluating knowledge” and “Balancing approaches”. Conclusions Nursing students do not automatically possess the ability to transfer knowledge from one setting to another; rather, their development is shaped by their experiences and interactions with others when they meet real patients. The study revealed different ways in which students navigated tensions related to power differentials. Reflecting on actions is a prerequisite for developing and learning practical skills and professional identities. This highlights the importance of both educators’ and the preceptors’ roles for socializing students in this process.